Posttransplant nephrotic syndrome resulting from NELL1‐positive membranous nephropathy. Issue 9 (8th May 2021) - Münch, Johannes; Krüger, Bastian M.; Weimann, Antje; Wiech, Thorsten; Reinhard, Linda; Hoxha, Elion; Pfister, Frederick; Halbritter, Jan
Abstract : Membranous nephropathy (MN) constitutes a major cause of nephrotic syndrome (NS) in adults. After kidney transplantation (KTx), both recurrent and de novo MN has been reported. In addition to PLA2R and THSD7A, recent identification of neural EGFL‐like‐1 protein, NELL1, as a potential disease antigen has enriched our understanding of MN pathogenesis. To date, NELL1‐positive MN has only been described in native kidneys, but never been diagnosed in renal allografts. We here report on a 56‐year‐old male kidney transplant recipient suffering from amyotrophic lateral sclerosis (ALS), who developed NS 25 years after KTx. Allograft biopsy revealed NELL1‐positive MN. Using specifically established immunoblotting techniques, we detected new‐onset NELL1‐IgG1, IgG3, and IgG4 antibodies in the patient´s serum correlating with the course of proteinuria. While primary renal disease was undetermined, MN recurrence seemed unlikely given the long‐time span since KTx. By clinical investigation of de novo etiologies, we did not detect an underlying malignancy. However, previous self‐medication with dimercaptopropane sulfonate (DMPS) and alpha lipoic acid (ALA) represented a potential trigger and cessation associated with partial remission of proteinuria. This report illustrates the first case of posttransplant NS due to NELL1‐positive MN. Monitoring NELL1 antibodies in the serum promise to be a non‐invasive diagnostic tool guiding disease management. Abstract : This unique case of posttransplant membranous nephropathy associated with new‐onset NELL1‐IgG autoantibodies identifiable in both the patient's serum and the allograft tissue.